Impact of Mobility Device Use on Quality of Life in Children With Friedreich Ataxia. (May 2018) - Ejaz, Resham; Chen, Shiyi; Isaacs, Charles J.; Carnevale, Amanda; Wilson, Judith; George, Kristen; Delatycki, Martin B.; Perlman, Susan L.; Mathews, Katherine D.; Wilmot, George R.; Hoyle, J. Chad; Subramony, Sub H.; et al.
Objective: To determine how mobility device use impacts quality of life in children with Friedreich ataxia. Study Design: Data from 111 pediatric patients with genetically confirmed Friedreich ataxia were collected from a prospective natural history study utilizing standardized clinical evaluations, including health-related quality of life using the Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Module. Results: Mobility device use was associated with worse mean PedsQL total, physical, emotional, social, and academic subscores, after adjusting for gender, age of disease onset, and Friedreich Ataxia Rating Scale score. The magnitude of the difference was greatest for the physical subscore (–19.5 points, 95% CI = –30.00, –8.99, P < .001) and least for the emotional subscore (–10.61 points, 95% CI = –20.21, –1.02, P = .03). Transition to or between mobility devices trended toward worse physical subscore (–16.20 points, 95% CI = –32.07, –0.33, P = .05). Conclusions: Mobility device use is associated with significant worsening of all domains of quality of life in children with Friedreich ataxia.